Neurophysiological advantages of biorelevant methodology of teaching academic disciplines - Natalia A. Davidovskaya (Открытое образование (Москва), 2017)
The analysis of technology of teaching a biorelevant lesson showed when using a traditional methodology of teaching (the sinistrocerebral one), there is a contradiction between social and biological aspects of the cerebrum functional system. It impels teachers to search for new methods of teaching on the basis of human reserves that have not been involved before. Personal development and education, as processes of forming higher mental functions, are considered in the article as complex forms of conscious activity, which are regulated by the corresponding aims and programs. It is shown that for comprehensive perception and fixing of the received information in memory, it is important that neural connections of cerebrum were maximally activated vertically (subcortex-cortex) and horizontally (left and right brain). In this connection, a cerebrum is considered as a complex metasystem consisting of macro- and microsystems incorporated into a multilevel organization with multiple horizontal and vertical relations. In such a system, the code of perceiving, processing and maintaining information is highly sought in the conditions of research activity and corresponds to a person’s instinct of self-preservation at most.  On the principle that the sinistrocerebral methodology of teaching, dividing reason and feelings, leads to “robotization” of an individual, disconnection with long-term memory, teleologism and natural instincts are disjoined. Further use of the sinistrocerebral methodology of teaching in the conditions of computerization of society threatens with degradation of the succeeding generations. The traditional method of teaching violates the genetic sequence of perceiving information and results in the functional disconnection in the integrative brain activity, forming the “tunnel of reality”, limited by short-term memory, on the one hand, and by the blinkered vision, on the other hand, that worsens the quality of life, psychological-emotional state and physical well-being of a person significantly. It is shown that a biorelevant method of teaching is developmental. Its application results in unveiling capabilities and potential possibilities of a person’s thinking and mind on a physical, creative, interpersonal, social levels, and on the levels of principles and world view, as well. Mentally stable individuals with integral thinking and are able to create a society with sustainable development that today is the aim of progressive intentions of humanity. At the present stage, the biorelevant method of teaching excels other methods of teaching in terms of biological adequacy and must be recommended by the Ministry of Education and Ministry of Health for obligatory application in practice of schools, higher educational institutions and other educational establishments.